2016
DOI: 10.1007/s00268-016-3471-8
|View full text |Cite
|
Sign up to set email alerts
|

Improving Minimally Invasive Adrenalectomy: Selection of Optimal Approach and Comparison of Outcomes

Abstract: Minimally invasive adrenalectomy is associated with expected excellent outcomes regardless of approach. In our series, the posterior approach is associated with decreased operative time and LOS. Robotic technology provides potential advantages for the surgeon at the expense of more complex setup requirements and costs. Further study is required to demonstrate clear benefit of one surgical approach. Utilization of the entire spectrum of available operative techniques can allow for selection of the optimal appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 42 publications
6
37
1
Order By: Relevance
“…In the present study, we compared the perioperative outcomes of three minimally invasive adrenalectomy approaches, including RATLA, TLA, and RLA in a highvolume center. Only a few previous studies exist that compare the results for all these three widely used techniques for minimally invasive adrenalectomy [20,21]. Although the potential advantages to the surgeon have been shown in robotic adrenalectomy, most studies have demonstrated that the robotic approach has non-inferior oncologic results and perioperative outcomes, when compared with the laparoscopic approach [22].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we compared the perioperative outcomes of three minimally invasive adrenalectomy approaches, including RATLA, TLA, and RLA in a highvolume center. Only a few previous studies exist that compare the results for all these three widely used techniques for minimally invasive adrenalectomy [20,21]. Although the potential advantages to the surgeon have been shown in robotic adrenalectomy, most studies have demonstrated that the robotic approach has non-inferior oncologic results and perioperative outcomes, when compared with the laparoscopic approach [22].…”
Section: Discussionmentioning
confidence: 99%
“…In these [11][12][13][14][15][16][17][18][19][20]. In light of the technical refinement and growing experience with MIA, we sought to perform a contemporary comparative analysis of surgical outcomes between OA and MIA for ACC [6,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies have been retrospective observational comparative studies, 13,14,[16][17][18][19][20][21][22][23][24]26 and only one of them was a randomized controlled trial. 15 One of the first series comparing LA with robotic adrenalectomy was by Morino et al who evaluated outcomes in 10 patients who underwent laparoscopic and robotic adrenalectomy.…”
Section: Ra Vs Lamentioning
confidence: 99%